ISLAMIC RELIGIOUS EDUCATION TEACHERS STRATEGIES FOR FOSTERING STUDENTS SOCIAL-CARE CHARACTER AT SMPN 1 LUWUK IN THE DIGITAL ERA - Citra Oktogia Fitri; Bidjai, Tomi; Abute, Erniwati La; Djayadin, Chairunnisa (UIN Antasari Banjarmasin, 2025)
This study aims to provide a comprehensive explanation of Islamic Religious Education (IRE) teachers strategies in developing students social care character, the challenges faced by teachers in shaping this character in the digital era, and the efforts undertaken by IRE teachers to overcome these challenges. The research employed a descriptive qualitative method with one IRE teacher and three students selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and then analyzed using the Miles and Huberman model, with validation achieved through source, technique, and time triangulation. The findings demonstrate that IRE teachers employ several strategies, including emotional and personal approaches, adaptive classroom management, peer influence, the integration of practical values and contextual learning, as well as the utilization of technology in the digital era. The main challenges include reduced social interaction and digital addiction, a gap between values and behavioral implementation (cognitive action gap), and the disintegration of the familys educational role. The teacher addressed these challenges through several efforts, namely limiting gadget use during learning activities, delivering humanistic and developmentally appropriate advice, building emotional closeness as a form of moral role modeling, collaborating with parents and the guidance and counseling unit, conducting qualitative and continuous character evaluation, and establishing strong teacher student relationships as the foundation for successful character education. This study emphasizes that the adaptive strategies implemented by IRE teachers, along with supportive learning environments, significantly determine the success of developing students social care character in the digital era. Keywords: Digital Era; Islamic Religious Education; Social Responsibility Character